(untitled) (Research, Society and Development, 2021)
Cereal bars have gained constantly growing interests because of their nutritional quality and practicality in consumption. To meet the increasing market needs, their formulation strategies are evolving with each passing day. Therefore, the present study aimed to develop a new formulation of cereal bars with baru almonds and pineapple peels, an agricultural waste, added in different quantities, or be 5.5% F1, 8.5% F2, and 9.5% F3. The developed bars were characterised for microbiological quality, sensory acceptability, and physico-chemical properties. The microbiological analysis identifying <10 CFU/ g of molds and yeasts on the bars indicated their suitability for human consumption. Further, their sensory evaluation revealed good acceptability and purchase intentions. The three formulations - F1, F2, and F3 - evaluated here were not significantly different; however, the average percentage of the acceptability index attributes of each formulation identified F2 as the best formulation. Subsequent physico-chemical analysis of F2 revealed the nutritional potential of the prepared bars with 50.1% carbohydrates, 3.44% fibres, 12.24% proteins and 19.25% lipids. Overall, these findings demonstrated that the improved nutrient composition of the prepared cereal bars is attributed to baru almonds and pineapple peels. This study paved the way for utilising industrial wastes and escalating the use of native fruits of Brazil to develop nutrient-rich convenient foods.